2011
DOI: 10.1007/s10695-011-9579-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pou2 ortholog in Chinese sturgeon, Acipenser sinensis and its expression patterns in tissues, immature individuals and during embryogenesis

Abstract: The class V POU family genes, including pou5f1 and pou2, encode transcription factors critical for the maintenance of pluripotency in embryonic stem cells (ESC) and germ line cells in vertebrates. In the present study, the full-length cDNA of a pou2 ortholog in A. sinensis, Aspou2, was cloned and sequenced. This cDNA sequence is 2,853 base pairs in length and encodes a peptide of 431 amino acid residues. A comparison of the deduced amino acid sequence of Aspou2 with that of other vertebrate species showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Nine ( zp3 , zpax , spermidine synthase, hatching enzyme, pou2 , Bucky ball , cyclin E , sox3 , and gdf9 ) were found to be up-regulated in ovary compared to testis, with the Vitrin-like gene showing higher expression in testis than in ovary, in accordance with the transcriptome analysis ( Table 3 ). Previous RT-PCR detection of the pou2 gene also suggested its higher transcription level in ovary [ 30 ]. These selected genes showed significant expression differences in ovary and testis, but at different levels from those found in transcriptome sequencing ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine ( zp3 , zpax , spermidine synthase, hatching enzyme, pou2 , Bucky ball , cyclin E , sox3 , and gdf9 ) were found to be up-regulated in ovary compared to testis, with the Vitrin-like gene showing higher expression in testis than in ovary, in accordance with the transcriptome analysis ( Table 3 ). Previous RT-PCR detection of the pou2 gene also suggested its higher transcription level in ovary [ 30 ]. These selected genes showed significant expression differences in ovary and testis, but at different levels from those found in transcriptome sequencing ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Chinese sturgeon transcriptome, nanos3b and the undifferentiated spermatogonia markers sox3 and oct4 were present, both with higher expression levels in the ovary compared to that in the testis ( S4 Table ). Our previous study revealed that oct4 ( pou2 ) was transcribed in gonads of immature Chinese sturgeons, including the testes of 1-year-old males that was primarily composed [ 30 ], indicating its possible role in the early development of spermatogonia. Besides, the meiosis specific markers of DNA meiotic recombinase 1 ( dmc1 ) and meiotic protein covalently bound to DSB ( spo11 ) [ 12 ] were also found in the present transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…However, a short motif with the consensus sequence (K/R)XWYXF was moderately well conserved in both POU2 and POU5F1 (Figure 1), the first time a sequence signature conserved in the N-terminal domain of all family members has been identified. The previously noted N-terminal sequence MAGH and the deletion of a single arginine residue within the POU-homeodomain [5], as well as an aspartic acid instead of glutamic acid at a site within the POU-specific domain identified by Ye and colleagues [13], were among the few fully conserved signatures specifically characterizing POU5F1 orthologs. We also noted that a second single-residue deletion in the linker region separating the POU-specific and POU-homeodomains of POU5F1 is specific to Boreoeutheria, as it was not present in the elephant (Afrotheria), armadillo (Xenarthra) or any other vertebrate (Figure 1), suggesting a modification in function of POU5F1 among some eutherians.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, POU2 is also differentially expressed in early tammar conceptuses [5] and protein immunolocalization suggests that POU2 is a more specific marker than POU5F1 of very early epiblast [20]. Interestingly in the sturgeon, pou2 transcripts were also detected in many adult tissues [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation